The Mishnah : religious perspectives - Neusner, Jacob, 1932- (Handbook of Oriental Studies. Section 1 The Near and Middle East, 1999)
Condensing research concerning questions of religion which encompass the social history of ideas and the religious uses of language, this book deals with three questions: the relationship of the Mishnah to Scripture, the relationship of the religious ideas people hold to the world in which they live, and the religious meaning of the formalization of language that characterizes the Mishnah in particular. In discussing how the Mishnah relates to Scripture - in the (later) mythic language of Rabbinic Judaism: \'the oral Torah\' to \'the written Torah\' - a complete analysis is presented, based on a systematic application of a single taxonomic program. Then an examination is made of how the stages in the unfolding of the Halakhah of the Mishnah relate to the principal events of the times, which delineate those stages. Here focus is given to those pre-70 C.E. components of the Halakhah that later come to the surface in the Mishnah, but discussion extends to the periods from the destruction of the Temple in 70 C.E. to the Bar Kokhba War, concluded in circa 135 C.E., then from the reconstruction, 135 C.E., to the closure of the Mishnah, 200 C.E. Finally attention is given to methods of interpreting the rhetorical forms of the Mishnah in the context of the social culture laid bare by the socio-linguistics of the documents concerned. This publication has also been published in paperback, please click here for details.